Air pollution and its effects on the immune system - Glencross, Drew A.; Ho, Tzer-Ren; Camiña, Nuria; Hawrylowicz, Catherine M.; Pfeffer, Paul E. (Free radical biology & medicine, 2020)
A well-functioning immune system is vital for a healthy body. Inadequate and excessive immune responses underlie diverse pathologies such as serious infections, metastatic malignancies and auto-immune conditions. Therefore, understanding the effects of ambient pollutants on the immune system is vital to understanding how pollution causes disease, and how that pathology could be abrogated. The immune system itself consists of multiple types of immune cell that act together to generate (or fail to generate) immune responses and in this article we review evidence of how air pollutants can affect different immune cell types such as particle-clearing macrophages, inflammatory neutrophils, dendritic cells that orchestrate adaptive immune responses and lymphocytes that enact those responses. Common themes that emerge are of the capacity of air pollutants to stimulate pro-inflammatory immune responses across multiple classes of immune cell. Air pollution can enhance T helper lymphocyte type 2 (Th2) and T helper lymphocyte type 17 (Th17) adaptive immune responses, as seen in allergy and asthma, and dysregulate anti-viral immune responses. The clinical effects of air pollution, in particular the known association between elevated ambient pollution and exacerbations of asthma and chronic obstructive pulmonary disease (COPD), are consistent with these identified immunological mechanisms. Further to this, as inhaled air pollution deposits primarily on the respiratory mucosa this review focuses on mechanisms of respiratory disease. However, as discussed in the article, air pollution also affects the wider immune system for example in the neonate and gastrointestinal tract. Whilst the many identified actions of air pollution on the immune system are notably diverse, immunological research does suggest potential strategies to ameliorate such effects, for example with vitamin D supplementation. An in-depth understanding of the immunological effects of ambient pollutants should hopefully yield new ideas on how to reduce the adverse health effects of air pollution. [Display omitted] •Air pollutants can perturb in vitro anti-microbial and regulatory immune responses.•Pollutants trigger inflammatory cytokine release from the epithelium and macrophages.•Particulates can enhance TH lymphocyte type 2 and 17 responses.•Consistent with the immunology, pollution is clinically associated with respiratory exacerbations.•Strategies such as vitamin D supplementation may ameliorate harmful immune effects.